Analisis Pengaruh Ukuran Perusahaan, Leverage, Kepemilikan Institusional, Kepemilikan Manajerial Dan Kualitas Audit Terhadap Manajemen Laba Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Periode 2017-2020 - Fatma Siti Kholifah; Nafi Inayati Zahro; Zaenal Afifi (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to determine the influence of analysis of the influence of company size, leverage, institutional ownership, managerial ownership and audit quality on audit quality in manufacturing companies listed on the Indonesian Stock Exchange in 2017-2020. This research uses a sample of manufacturing companies listed on the Indonesian Stock Exchange 2017-2020. The sample used was calculated based on the purposive sampling method. Research data was taken from the annual reports of research sample companies published by the IDX. The sample for this research was 92 company data. Data analysis calculations used multiple regression analysis which was calculated using SPSS 25. The research results found that audit quality had a negative effect on audit quality. Company size, leverage, institutional ownership and managerial ownership do not have a significant effect on audit quality.